PENGARUH HIDROLISIS ENZIMATIS TERHADAP PRODUKSI BIOETANOL DARI UMBI TALAS (Colocasia gigantea Hook F) - Marniati Salim; Elida Mardiah; Febby Febrizal (Jurnal Riset Kimia, 2012)
Umbi talas (Colocasia gigantea Hook F) are rich of starch (77.9%), that could be fermentated to form bioethanol for reneweable energy. The ethanol were produced by fermenting the hydrolised enzymaticly by Î±-amylase and glucoamylase at the variation 4, 5, 6, 7, and 8 mL for 1, 2, 3, 4, and 5 hours. The glucose produced was measured by Somogy-Nelson methode. The product of hydrolysed were optimum with 6 mL Î±-amylase and 7 mL glucoamylase for 4 hours wich gave 64,222 g/L of reducing sugar. The product of ethanol were analyzed by Gas Chromatography (GC). The maximum bioethanol production obtained after 5 days fermentation was 4.0123%.